2016
DOI: 10.1021/acs.jmedchem.6b00297
|View full text |Cite
|
Sign up to set email alerts
|

New 6-Aminoquinoxaline Derivatives with Neuroprotective Effect on Dopaminergic Neurons in Cellular and Animal Parkinson Disease Models

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder of aging characterized by motor symptoms that result from the loss of midbrain dopamine neurons and the disruption of dopamine-mediated neurotransmission. There is currently no curative treatment for this disorder. To discover druggable neuroprotective compounds for dopamine neurons, we have designed and synthesized a second-generation of quinoxaline-derived molecules based on structure-activity relationship studies, which led previously to the discovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…14 We reported before that the phenyl ring located at position 3 of the quinoxaline core was essential for neuroprotection by 6-aminoquinoxalines 13 and that the lack of substituent at position 2 was apparently crucial to optimize this activity. 14 Therefore, we designed a specific convergent route for the preparation of 3-aryl-1,4,8-triazaphenanthrenes 5c, 5f, 5g, 5k-o, based on a palladiumcatalyzed Suzuki coupling reaction of aryl-boronic acids or boronate esters with 3-chloro-1,4,8-triazaphenanthrene 5i. Compound 5j was prepared from a Sonogashira cross-coupling with TMS-acetylene followed by methanolysis (Scheme 1).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…14 We reported before that the phenyl ring located at position 3 of the quinoxaline core was essential for neuroprotection by 6-aminoquinoxalines 13 and that the lack of substituent at position 2 was apparently crucial to optimize this activity. 14 Therefore, we designed a specific convergent route for the preparation of 3-aryl-1,4,8-triazaphenanthrenes 5c, 5f, 5g, 5k-o, based on a palladiumcatalyzed Suzuki coupling reaction of aryl-boronic acids or boronate esters with 3-chloro-1,4,8-triazaphenanthrene 5i. Compound 5j was prepared from a Sonogashira cross-coupling with TMS-acetylene followed by methanolysis (Scheme 1).…”
Section: Resultsmentioning
confidence: 98%
“…Finally, we also established that when given orally, PAQ was providing protection to DA neurons and their striatal terminals in a rodent model of PD. 14 At this stage, we decided to explore the neuroprotective potential of 1,4,8-triazaphenanthrenes derived synthetically from 6-aminoquinoxalines. Indeed, we recently reported that the 6-endo-dig cycloisomerization of N-propargyl-6-aminoquinoxalines leads to the expected 1,4,8-triazaphenanthrenes in a highly regioselective manner.…”
Section: Introductionmentioning
confidence: 99%
“…The authors further demonstrated that 6-OHDA reduced the spike number and rheobase of DA neurons in acute brain slices, effects that were also reversed by RyR blockade. Furthermore, novel 6-aminoquinoxaline derivatives appear to confer neuroprotective effects on DA neurons in cellular animal models of PD that are at least partially mediated through interactions with RyRs [110]. Interestingly, blocking Ca 2+ influx did not change PCB effects on intracellular dopamine levels in a catecholaminergic cell line [87], suggesting that PCBs may be more likely affecting dopamine homeostasis by mediating dysfunction of ER Ca 2+ stores.…”
Section: Evidence That Pcbs Alter Ca 2+ Channel Function and Ca 2+ -Dmentioning
confidence: 97%
“…Parkinson’s disease is characterized by a loss of dopaminergic neurons, depletion of dopamine and mitochondrial dysfunction resulting in oxidative and excitotoxic stress (Hirsch et al, 2013 ). Recently, a new compound which showed neuroprotective effects in dopaminergic neurons, was tested in a Parkinson’s disease mouse model (Le Douaron et al, 2016 ). The neuroprotective effects of this compound could be partially counteracted by dantrolene, suggesting this compound operates in part by activating RyR-mediated Ca 2+ signaling.…”
Section: The Ryr In Neurodegenerative Diseasesmentioning
confidence: 99%